Kualitas Organoleptik Sosis Telur Itik Dengan Penambahan Wortel (Daucus Carota L.) - Nabila, Mala Maulia; Monica, Metha; Fatati, * (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to determine the organoleptic quality of duck egg sausage with the addition of carrots (Daucus carota L.). The study was conducted at the Laboratory of the Faculty of Animal Husbandry, Jambi University on November 24 to December 23, 2025. The design used was a Randomized Block Design (RAK) with 5 treatments and 30 semi-trained panelists as a group. The treatment consisted of a ratio of 100% duck eggs with the addition of carrots successively at 25% (P1), 35% (P2), 45% (P3), 55% (P4), and 65% (P5). The parameters observed included color, aroma, texture, and taste using a hedonic scale of 1–5. Data were analyzed using One Way Analysis of Variance (ANOVA) with the help of the SPSS program. The results showed that the addition of carrots at various treatment levels did not provide significant differences (P>0.05) on the color, aroma, texture, and taste of duck egg sausage. This study concluded that the addition of carrots up to 65% showed the same organoleptic quality of duck egg sausage based on panelist assessments.